The role of the cost system by activities in managing cost and supporting the competitiveness of economic institutions - chalabi, amar (Journal of Research in Finance and Accounting, 2019)
The aim of this research to identify the system cost by activities (ABC), as this system of modern systems that aim to address the shortcoming of the traditional system, The effective management of the cost requires the use of a set of tools and methods in order to reduce the control of cost ,The study sought to realize the Demonstration of requirements of applying the procedures of the (ABC) ,The study arrived at many conclusions in relation to the products costing body and the change in its profit.